Isolamento de bactérias de solo subtropical com capacidade de promoção de crescimento vegetal - Matter, Juliana Maria (2015)
Chemical fertilizers management in agriculture is the main source of nutrients for crops development aiming at increasing yield. Thus, phosphorus, among other nutrients, is required by plants since it is the most limiting mineral on yield crops of commercial interest, because of its low availability and immobility in soil, as it also gets unavailable to absorption by the plants. Studies have shown that phosphate solubilization up from bacteria inoculation can improve agricultural production. Many bacteria can take part on the dissolution process through different mechanisms and promote plant growth either by dissolving phosphates or determining nitrogen (N) and indole acetic acid production (IAA). Due to the isolation of these microorganisms, they can be inoculated and make the fixed phosphorus available, reducing the use of fertilizers or readjusting excessive percentages of this element in their formulas to improve a development of sustainable agricultural yield. According to this theme, it was possible to apply a methodology for the isolation of subtropical soil bacteria with maize cropping from different soil fertilization managements. After isolating the micro-organisms, they were submitted to endurance tests after pricking, phosphatase production ability, IAA production with and without L-tryptophan and identification method by rDNA extraction technique. A greater diversity of mineralizing bacteria was found in treatment 1 soil (no fertilization). The results related to the largest percentage increase in Calcium phytate can be justified by the fact that bacterial communities can produce enzymes. The stability of the solubilizing function was greater in calcium phytate when compared to the other culture media that have been used. The study has indicated that soil microbiota keeps a similarity in which Ochrobactrum gender has prevailed and under different management situations, its diversity slightly varies, but it is able to produce metabolites promoters of plant growth; while the isolates of Treatment 2 (mineral fertilization) have kept the best acid phosphatase production. The IAA production, without L-tryptophan addition in T1, suggests that the microbiota uses metabolic pathways for different purposes, since the studied soil is poor in minerals, thus it affects the production of plant growth promoters. It differs from Treatment 3 that received fertilization with swine wastewater, and diversified IAA production for its isolates with stronger values. With this study it was possible to identify genera of bacteria with high phytate mineralization capacity. At last, according to the study results, it was possible to identify the bacteria genera with high capacity to mineralize phytate and produce IAA, indicating the promotion of vegetal growth capacity.